o ensino da lingua brasileira de sinais para crianças ouvintes na educação infantil - Oliveira, Daiane Pond (Brasil, 2023)
This research had as general objective the teaching of Libras to hearing students in the second period of kindergarten in the municipal network of Parintins-AM. We had as specific objectives to identify which methodologies and resources are used in teaching Libras to these students and to identify the conversation/socialization with the use of Libras among students. The methodology adopted was action research and qualitative research through an interview with the class teacher. We talk about how the choice of built materials was made, and how these materials were applied. With the results obtained, it was seen that the children used Libras in their daily life at school and in socializing with their classmates. With the teacher's interview, we realized the need to offer Libras in early childhood education, as this is the awareness that we must have about the relevance of learning Libras to promote the social inclusion of the deaf community and make its communication more efficient and meaningful.